Effects of smoking on skin conditions: in vivo assessment - Ab. Hadi, Hazrina; Razak, Luqman (2018)
INTRODUCTION: Tobacco smoking was associated with the acceleration of skin aging rate. Low hydration status and trans epidermal water loss (TEWL), elasticity loss and reduction in epidermis thickness were the characteristics observed upon aged skin. OBJECTIVES: The study was aimed to analyze the effect of smoking on the skin conditions. METHODS: In vivo skin assessment using non-invasive technique via DermaLab® Combo was conducted on 30 volunteers. 22 of them were smokers and 18 were non-smokers. TEWL, skin hydration, elasticity and skin dermal thickness were assessed in the study. The results were compared in terms of the smoking status, age group, years of smoking and amount of cigarette consumption per day. SPSS Version 22 was used and the one-way ANOVA were performed to analyse the results. RESULTS: From the study, it was observed that TEWL, elasticity and skin thickness between the group were not significantly difference between smokers and non-smokers. Smokers were found to have significant higher hydration level compared to that of non-smokers. TEWL and skin thickness were not significantly differed among the age group. However, there were significant difference in elasticity in the 18-30 years old group, 31-40 years old group, 41-50 years old group and 51-60 years old group when each group were compared to 61-70 years old group. This shows that elasticity level decreased as the age increased. Years of smoking produced significant difference in term of elasticity level when the smokers who smoked 1-10 years, 11-20 years and 21-30 years were compared each with the smokers who smoked more than 30 years. This suggests that as the period of cigarette exposure increased, the elasticity level would be decreased. CONCLUSION: In conclusion, tobacco smoking habit could influence the TEWL, skin hydration, elasticity and skin dermal thickness which directly would affect the rate of skin aging.